2016
DOI: 10.1089/neu.2015.4186
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Binding Protein 5 Modulates Docosahexaenoic Acid-Induced Recovery in Rats Undergoing Spinal Cord Injury

Abstract: Omega-3 polyunsaturated fatty acids (n-3 PUFAs) promote functional recovery in rats undergoing spinal cord injury (SCI). However, the precise molecular mechanism coupling n-3 PUFAs to neurorestorative responses is not well understood. The aim of the present study was to determine the spatiotemporal expression of fatty acid binding protein 5 (FABP5) after contusive SCI and to investigate whether this protein plays a role in n-3 PUFA-mediated functional recovery post-SCI. We found that SCI resulted in a robust s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Given that FABP5 has been shown to be up‐regulated by DHA (Figueroa et al . ), the reduced FABP5 at the BBB in APP/PS1 mice could also be secondary to lower plasma levels of DHA. Indeed, lower DHA levels in the liver have been reported in 3‐month‐old APP/PS1 mice compared to WT littermates (Perez et al .…”
Section: Discussionmentioning
confidence: 97%
“…Given that FABP5 has been shown to be up‐regulated by DHA (Figueroa et al . ), the reduced FABP5 at the BBB in APP/PS1 mice could also be secondary to lower plasma levels of DHA. Indeed, lower DHA levels in the liver have been reported in 3‐month‐old APP/PS1 mice compared to WT littermates (Perez et al .…”
Section: Discussionmentioning
confidence: 97%
“…A 1.7‐fold increase in brain microvascular FABP5 expression was identified in mice fed the DHA‐enriched diet, compared to the control group, which is in agreement with a previous study, where spinal cord FABP5 gene expression elevated twofold in rats fed a DHA‐enriched diet for 8 weeks (Figueroa et al . ). The higher fold increase in FABP5 expression observed in the mouse dietary intervention study than the in vitro study could be explained by the longer term of exposure to higher levels of DHA.…”
Section: Discussionmentioning
confidence: 97%
“…Spinal cord FABP5 gene expression elevated twofold in rats fed a DHA‐enriched diet for 8 weeks (Figueroa et al . ). Therefore, DHA has the potential to up‐regulate BBB expression of FABP5 and help to facilitate its own transport across the BBB.…”
mentioning
confidence: 97%
“…Former study has demonstrated that the ketogenic diet improves forelimb motor function after spinal cord injury in rodents [17]. And Omega-3 polyunsaturated fatty acids could promote functional recovery in rats undergoing spinal cord injury [18]. So, GHSR could be related to neurological injury and the neurotrophin-3 treatment by regulating the cellular ketone metabolic process and fatty acid metabolic process.…”
Section: Discussionmentioning
confidence: 99%